2013
DOI: 10.1016/j.eats.2013.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic Posterior Labral Repair and Capsular Shift With a Lateralized Posterior Portal

Abstract: Arthroscopic techniques for posterior shoulder subluxation with labral injuries in athletes have shown good results. The difficulty with the procedure is gaining appropriate access to the posteroinferior quadrant of the glenoid at a steep enough angle that allows for safe anchor placement. Various portals have been described that can be used as accessory portals for anchor placement. Although the use of additional portals to create appropriate access to the joint is always encouraged, preoperative planning can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 14 publications
0
5
0
2
Order By: Relevance
“…Rather, in many cases, significant abrasions and degenerations can be observed in the posteroinferior labral area. 8,10,16,29 Based on the postoperative results in the literature, arthroscopic posterior labral refixation delivers good results in terms of both recurrence (2.4%-8%) and returnto-sport rate. 1,2,5,15,16,24,29 It is worth noting, however, that the rate of return to sport at the preinjury level is lower for throwing athletes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather, in many cases, significant abrasions and degenerations can be observed in the posteroinferior labral area. 8,10,16,29 Based on the postoperative results in the literature, arthroscopic posterior labral refixation delivers good results in terms of both recurrence (2.4%-8%) and returnto-sport rate. 1,2,5,15,16,24,29 It is worth noting, however, that the rate of return to sport at the preinjury level is lower for throwing athletes.…”
Section: Discussionmentioning
confidence: 99%
“…There are 2 solutions for this: one is to create a complementary posterolateral portal, placed distally and laterally from the standard posterior portal, and the other solution is to place a standard posterior portal 1 cm distally and 1 to 2 cm laterally from its original position. 8 , 16 , 24 , 25 We usually create the standard portal more distally and laterally; depending on the position and size of the labral injury, we decide whether to create a complementary posterior portal during the operation. Anatomic studies indicate that the complementary posterior portal is located very close to the axillary nerve, which runs closest to the glenoid rim at the 6-o’clock position.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other investigators have suggested alternative portals for access to the posterior and inferior labrum. Ciccone 12 reported on his use of a lateralized posterior portal without use of accessory portals for fixation of posterior labral tears, and the posterolateral accessory portal, as well as a low posterolateral portal, has been described—all used with the purpose of gaining a proper angle for anchor placement. 6 Any of these described portals can be used at the surgeon's discretion, as long as the entire labrum is visualized, with the correct trajectory achieved for anchor placement circumferentially.…”
Section: Discussionmentioning
confidence: 99%
“…Several techniques have been identified to facilitate posterior glenoid anchor placement and repair of the posterior labrum. 5,6,[11][12][13][14] Adequate tissue preparation, including liberation and mobilization of the capsulolabral complex and debridement of the glenoid rim, is also believed to be critical to achieving a successful repair and optimized outcomes. Commonly, this is performed from 1 of 2 established anterior portals or directly from the posterior portal.…”
mentioning
confidence: 99%